Dementia With Lewy Bodies (Dlb) Diagnosis Rates vs. National Benchmarks: A Completed Audit Cycle in Manchester Memory Services - Ahmed Ghaly; Eleni Markopoulou (BJPsych Open)
Aims: Dementia with Lewy Bodies (DLB) is a progressive neurodegenerative disorder accounting for 5–15% of dementia cases. A 2022 audit at Manchester’s Memory Assessment and Treatment Services (MATS) identified DLB diagnosis rates of 2%, significantly below national benchmarks, prompting recommendations for greater awareness and the potential use of the DIAMOND Lewy Toolkit. This re-audit aimed to: